Abelmoschus manihot for Diabetic Nephropathy: A Systematic Review and Meta-Analysis. (18th April 2019) - Shi, Liwei; Feng, Ling; Zhang, Meizhen; Li, Xiaowen; Yang, Yanan; Zhang, Yueying; Ni, Qing
Abstract : Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD). Many trials have shown that Abelmoschus manihot could further improve proteinuria and protect kidney function in patients with DN when added to a renin-angiotensin system (RAS) blocker. A systematic assessment of the efficacy and safety of A. manihot in DN is essential. Eight electronic databases were searched to identify eligible trials published from inception to December 2017. The Cochrane Risk of Bias Tool was used to evaluate the methodological quality of eligible studies. Seventy-two studies with 5, 895 participants were identified. The methodological quality of included studies was generally low. The results indicated that, compared to a RAS blocker, combined treatment of A. manihot with a RAS blocker was more effective for 24h urinary protein (24h UP) (mean difference [MD], -0.39 [95% confidence interval [CI], -0.46 to -0.33] g/d; P<0.00001), urinary albumin excretion rate (UAER)(MD, -19.90 [95% CI, -22.62 to -17.18] μ g/min; P<0.00001), 24h UP reduction rate (risk ratio [RR], 1.43; 95% CI, 1.26-1.63; P<0.00001), normalization of UAER (RR, 1.48; 95% CI, 1.29-1.70; P<0.00001), and serum creatinine (SCr) (MD, -7.35 [95% CI, -9.95 to -4.76] umol/L; P<0.00001). None of these trials reported the ESRD rate. No statistically significant difference occurred between A. manihot combined with a RAS blocker and a RAS blocker alone in estimated glomerular filtration rate (eGFR) (MD, 4.43 [95% CI, -1.68 to 10.54] mL/min; P=0.16). A. manihot did not increase the rates of adverse drug events. A. manihot in addition to a RAS blocker was effective and safe to further improve proteinuria and protect kidney function in patients with DN. However, due to the generally low methodological quality, significant heterogeneity, and publication bias, high-quality randomized controlled trials are required to confirm these findings before the routine use of A. manihot can be recommended.